Purification and characterisation of angiotensin I converting enzyme (ACE) inhibitory peptide from blood cockle (Anadara granosa) meat hydrolysate - Aishah Suhaimi; Amiza Mat Amin; Norizah Mhd Sarbon; Mohd Effendy Abd. Wahid; Zaliha Harun (Penerbit Universiti Kebangsaan Malaysia, 2020)
Blood cockle (Anadara granosa) is the most abundant and available bivalves in Malaysia. Blood cockles meat has high protein content and has potential to generate bioactive peptides. To date, no study has been reported on purification and identification of angiotensin I converting enzyme (ACE) inhibitory peptides from blood cockle meat. Thus, the objectives of this study were to purify and characterize ACE inhibitory peptide from blood cockle meat hydrolysate. ACE inhibitory peptides from blood cockle meat hydrolysate (CMH) were prepared by enzymatic protein hydrolysis using Protamex®. Crude CMH was characterized for its stability against gastrointestinal proteases, at varying pH (2–11) and temperature (4–90°C). Next, crude CMH was purified by ultrafiltration, ion exchange chromatography and reverse-phase chromatography and its amino acid sequence was identified. It was found that crude CMH was highly stable at low pH and temperature, and was resistant to gastrointestinal proteases (pepsin and trypsin). A three-step purification increased the inhibitory activity of CMH, reducing its IC50 from 0.35 mg/ml to 0.0094 mg/ml. The amino acid sequence of the purified peptide was determined as VNDLLSGSFKHFLY, with a molecular weight of 1621.88 Da. This study suggested the potential of ACE inhibitory peptide derived from cockle meat as a nutraceutical ingredient in functional food.